Effects of Salinity on the Growth Performance and Nutritional Composition of Artemia - Xiaodong JIANG; Ying WANG; Hongyan LI; Xinfeng ZHANG; Xiao FENG; Chen ZHONG; Yuanqin SUN (Progress in Fishery Sciences)
Artemia is widely distributed in inland salt lakes and coastal salt fields around the world, has high nutritional value and strong palatability, and has been used as high-quality biological bait in aquaculture for a long time. Artemia can also be used as a food ingredient. Native Americans collect large quantities of Artemia, which are dried and processed into food; Libyans regard Artemia as a high-quality protein source rich in beta carotene and riboflavin and use it to make bread for sale as a delicacy. There are also reports in China that the enzymatic hydrolysate of Artemia eggs is used as a raw material to process amino acid beverages. Artemia has gradually shown great development prospects in the food industry. The growth of Artemia is mainly influenced by factors such as salinity, temperature, pH, dissolved oxygen, and light. These factors also affect physiological functions such as osmotic pressure, oxygen consumption rate, ammonia excretion rate, and reproduction to certain extents. Among them, salinity is an important factor affecting the physiological response of Artemia. Under salinity stress, the body of Artemia maintains its normal physiological functions by regulating osmotic pressure balance. The regulation of osmotic pressure balance mainly achieves ion transport through related metabolic enzymes and transporter proteins. This reverse transport process requires a large amount of energy, which comes from sugars, lipids, and proteins in the body. Therefore, the influence of salinity on the physiological functions of Artemia leads to changes in their nutritional composition, thereby affecting their growth performance and nutritional quality. Experiments were carried out in order to study the effects of different salinities on the growth performance and nutritional value of Artemia and explore its potential as raw material to develop marine food. Artemia was cultured under four different salinities (30, 60, 90, and 120) for 14 days. The body length, basic nutritional components, amino acid composition, fatty acid composition, and mineral contents of Artemia were measured and nutritional evaluations were conducted. The results showed that the body length of Artemia significantly varied under different salinities on day 14. Artemia in the salinity 30 group had the longest body length (2.05 cm) with average and specific growth rates of 0.93 mm/d and 7.65%/d, respectively. The nutritional composition of Artemia also significantly varied under different salinities, with crude protein, crude fat, ash, amino acid, and fatty acid contents ranging from 28.94% to 47.27%, 5.89% to 13.62%, 24.63% to 34.28%, 16.05 g/100 g to 37.22 g/100 g, and 2.06 g/100g to 5.48 g/100g, respectively. Among them, the salinity 30 group Artemia had the highest crude protein (47.27%) and amino acid (37.22 g/100 g) contents. Artemia in the salinity 30 group contained eight essential amino acids, which accounted for 43.42% of total amino acids, with flavor amino acids accounting for 49.52% and the first limiting amino acid being cysteine+methionine. High glutamate, leucine, and arginine contents of Artemia were observed in the salinity 30 group, with a balanced amino acids composition and an amino acid score of 91.79, which is in line with the ideal protein model recommended by the Food and Agriculture Organization/World Health Organization. Artemia in salinity 120 group had the highest crude fat (13.62%) and fatty acid (5.48 g/100 g) contents, with 2.11 g/100 gMUFA and 1.68 g/100g PUFA, respectively. EPA content was 1.13 g/100 g. Salinity levels significantly affected the mineral contents of Artemia, with the salinity 60 group showing the highest calcium, sodium, and iron contents and the salinity 90 group having the highest zinc content. In summary, the growth performance and nutritional value of Artemia in the salinity 30 group were the best. At this salinity level, the body length of Artemia were high, the growth rate was fast, and the growth performance was good. Artemia was rich in protein with balanced composition and delicious taste. Unsaturated and polyunsaturated fatty acids accounted for over 60% and 30% of the total fatty acids, respectively. Salinity significantly affected the average body length and nutritional composition of Artemia. The salinity 30 group had the longest average body length and highest protein and amino acid contents, whereas the 120 salinity group had the highest fatty acid content. Artemia is rich in protein and has a reasonable amino acid composition, making it a high-quality source of food protein. It has high nutritional value and enormous potential in the food industry. China has abundant Artemia resources; reasonable and efficient utilization of Artemia resources, research and development of Artemia-related nutritional foods, and further extension of the Artemia industry chain have great potential.